Hydrographic surveys – The purpose and the choice of scale - Day, Archibald (The International Hydrographic Review, 2025)
This manuscript is a reprint of the original paper previously published in 1955 in The International Hydrographic Review (IHR, https://ihr.iho.int/): Day, A. (1955). Hydrographic surveys – The purpose and the choice of scale. The International Hydrographic Review, 32(1), 9–24. https://journals.lib.unb.ca/index.php/ihr/article/view/26749